KARAKTERISTIK TULISAN NARASI FIKSI BERBAHASA ARAB MAHASISWA PENUTUR ASLI BAHASA INDONESIA - Nurhidayati Nurhidayati (Fakultas Sastra Universitas Negeri Malang, 2011)
This study is carried out to answer the research questions what are the characteristics of intrinsic elements, include is plot, character, and background of the Arabic fictitious narrative writing of Indonesian language native students? This study is qualitative. The approach used is socio-psycho structural. Data are verbal such as: (1) fictitious narrative writing, (2) interview transcript, and (3) fieldnotes. Data of fictitious narrative writing were taken from of the students’ portfolio writing narative fiction of final tasks semester of writing lucture 1. Data of interview transcript and fieldnotes of the teaching process are data used to clarify and complete the data of fictitious narrative writing. Data were analyzed using interactive analysis. Based on the findings be concluded that first, plot linier is domination plot in the writing fiction, Neaming character and fisiologis description is domination character was described as direct and non-direct description, and story background is domination background with used to descriptive of location and time of story without psichologis meaning.